Prevalence, Impact and Attitudes Toward Lower Gastrointestinal Dysmotility and Sensory Symptoms, and Their Treatment in Canada: A Descriptive Study - Richard H Hunt; Surinder Dhaliwal; Gervais Tougas; Carmen Pedro; Jean-Francois Labbé; Heidi Paul; Michael Ennamorato (Canadian Journal of Gastroenterology)
OBJECTIVES: To investigate the impact of lower gastrointestinal (GI) symptoms in the general Canadian population, and to explore patient satisfaction with traditional therapies and the level of patient interest in new treatments.